Analysis The Use of Adjective in The Novel "Harry Potter and The Cursed Child Part One and Two" - Dhesi - Fitria (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
In this study, the novel created by the novelist, J.K. Rowling, entitled “Harry Potter and The Cursed Child” Part One and Two is chosen to be analysed. The reasons why this novel was selected for research are (1) The novel uses the complex language so it contains form and variative adjective meaning. (2) The novel has not ever been researched so it will be something discovered. It has the perfect sentence structure and the complex part of speech, including adjective. The novel has the various parts of speech and one which will be analysed is adjective because it is a kind of unique part of speech. Adjective is vary based on the form and types. The knowledge about the meaning is still rare because of the minimum of researchers who research the problem. The methodology used in analysing this study is descriptive qualitative. The research is aimed to describe the form and adjective meaning. The essence of this study is about adjective as part of speech. Learning about adjective is always interesting because it has the complex meaning and boundaries. Adjective is a word that describes a person or thing, for example, big, red and clever, in a big house, red wine and a clever idea (Oxford, 2006:16). The figure in this novel, Harry Potter, is a cursed child which having adventure in a curse school named Hogwarts. In this novel, “Harry Potter and The Cursed Child” Part One and Two there are so many adjectives found. By the undergoing of this study, it is expected that this study has the benefits for everyone who wants to learn deeper about adjectives.